Izbrani teoretski vidiki razumevanja prostora kot elementa etnične, narodne in nacionalne identitete - Mlekuž, Jernej (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2001)
Space - along with time - is a dimension which cannot be erased from the social science and humanistic thought. Due to its "vast" and "evasive" nature, individual professions and experts are reluctant to deal with it. Thepresent text does not wish and is also unable to convey a clear picture on this, not only proverbially, "infinite" complex of ideas and concepts, restricting itself to a relatively narrow significance of space as a componentof ethnic and national identity. It is therefore necessary to highlight certain wider theoretic interpretations in this complex of "space", especially those referring to the relations between space and society.
Keywords: prostor (sociologija); identiteta; etničnost; narodna identiteta; kulturna identiteta